RNF4 Regulates the BLM Helicase in Recovery From Replication Fork Collapse - Ellis, Nathan; Zhu, Jianmei; Yagle, Mary K; Yang, Wei-Chih; Huang, Jing; Kwako, Alexander; Seidman, Michael M.; Matunis, Michael J. (Frontiers in Genetics, 2021)
Sumoylation is an important enhancer of responses to DNA replication stress and the SUMO-targeted ubiquitin E3 ligase RNF4 regulates these responses by ubiquitylation of sumoylated DNA damage response factors. The specific targets and functional consequences of RNF4 regulation in response to replication stress, however, have not been fully characterized. Here we demonstrated that RNF4 is required for the restart of DNA replication following prolonged hydroxyurea (HU)-induced replication stress. Contrary to its role in repair of -irradiation-induced DNA double-strand breaks (DSBs), our analysis revealed that RNF4 does not significantly impact recognition or repair of replication stress-associated DSBs. Rather, using DNA fiber assays, we found that the firing of new DNA replication origins, which is required for replication restart following prolonged stress, was inhibited in cells depleted of RNF4. We also provided evidence that RNF4 recognizes and ubiquitylates sumoylated Bloom syndrome DNA helicase BLM and thereby promotes its proteosome-mediated turnover at damaged DNA replication forks. Consistent with it being a functionally important RNF4 substrate, co-depletion of BLM rescued defects in the firing of new replication origins observed in cells depleted of RNF4 alone. We concluded that RNF4 acts to remove sumoylated BLM from collapsed DNA replication forks, which is required to facilitate normal resumption of DNA synthesis after prolonged replication fork stalling and collapse.